HIV/AIDS na infância: Representações sociais elaboradas por profissionais de saúde - Souza, Lisandra Ferreira de (2018)
Health professionals play an important role in supporting children living with HIV / AIDS, as they are responsible not only for clinical care, but also contribute to the promotion of quality of life and well-being. The professional team often has the role of mediating and guiding the care of family members with the children. Health professionals are also sought by families and users to share feelings and experiences, which contributes to the process of forming social representations about the phenomenon of AIDS in childhood. This study aimed to analyze the social representations about AIDS in childhood by professionals of a referral hospital, as well as the work of these professionals in the care of children living with HIV / AIDS. Therefore, two studies were carried out, according to the respective objectives: 1) To apprehend the social representations about AIDS in childhood by professionals of a reference hospital in the care of children living with HIV / AIDS; 2) To analyze the perception of professionals of a reference hospital on the role of children living with HIV / AIDS. It is a research of the exploratory and descriptive type, with a qualitative approach. Participants were 40 health professionals from a reference hospital, selected in a non probabilistic manner and for convenience. The instruments adopted were a sociodemographic and labor questionnaire and a semi- structured interview. The data derived from the sociodemographic and labor questionnaire were analyzed through descriptive statistics (frequency and percentage), and the data derived from the interviews were analyzed through content analysis of the thematic category type. In the first study, the data showed four thematic categories and eleven subcategories. Of the 116 units of content, 50.8% corresponded to the category Representations about living with AIDS in Childhood. The social representations focused on the experience of AIDS in childhood associated with symptoms and treatment, social vulnerability, as well as on the limitations of health services to attend this age group and people living with AIDS. In the second study, four thematic categories were evidenced, which covered twelve subcategories. Among the 109 content units, 40.2% correspond to the category of professional performance. The other categories were about feelings, difficulties in acting and sharing care with Primary Care. The difficulties of children living with AIDS and their families are not restricted to the physiological aspects associated with the disease and treatment. But it does encompass challenges in terms of coping with bias, including that of health professionals. In addition, professional action with children goes beyond the technical dimension of clinical care or the way services are arranged. But we want to consider the social, economic and public policy aspects necessary to overcome health inequities